Quels enseignements peut-on tirer du PISA : l’exemple des écarts de performances entre les sexes - Maciej Jakubowski; Francesca Borgonovi (Recherches en Éducation)
The paper explores how PISA data can be used to analyze cross-country variations in the gender gap in academic performance and the attitudes and behaviors of 15-year-old boys and girls. Concern about gender differences in education in much of the twentieth century focused on the disadvantage and underachievement of girls. More recently, however, the underachievement of boys in reading and the underachievement of girls in mathematics have become the focus of policy attention. The paper shows how PISA data can be used to inform the design of policies aimed at reducing gender gaps in education. The paper shows how gender differences are surprisingly similar across countries that participate in PISA. Boys are more often found among top achievers in mathematics and science, but also among those who lack basic skills in reading. Achievement differences, however, are not related to career choices. Even girls performing very high in mathematics rarely expect to work in science, technology, engineering and mathematics (STEM fields). Attitudes and beliefs seem to play a more important role in shaping gender differences in professional careers.